ABOUT DISTRIBUTION ON THE GRANULE SIZE IN NANOCOMPOSITES - A. N. Yurasov (Российский технологический журнал, 2016)
In this work we have presented the theoretical study of the size grain distribution in nanocomposites. The importance of the consideration of distribution, its relation with the size effect, influencing the theoretical description of nanocomposite optical and magneto-optical spectra, mainly in the near-IR region have been demonstrated. It has been also shown that the size effect can change the amplitude, form and sign of the optical and magneto-optical spectra. We have developed the formulas for the size effect as well as considered the distribution applications for the correct description of the optical and magneto-optical properties with regard to the grain size effect.